Older adults show a reduced tendency to engage in context-dependent decision biases. (May 2020) - Sablotny-Wackershauser, Verena; Betts, Matthew J.; Brunnlieb, Claudia; Apostolova, Ivayla; Buchert, Ralph; Düzel, Emrah; Gruendler, Theo O.J.; Vogt, Bodo
Abstract: When we make decisions, we usually consider the context. This can sometimes lead to suboptimal choices or choice abnormalities. One such abnormality is the compromise effect, according to which deciders tend to favour options positioned as a compromise in an available set of extreme options. Theoretical accounts consider that these effects relate to available cognitive resources, which, in turn, have been found to depend on an individual's dopaminergic innervation. Referring to a correlative triad between cognition, dopamine and aging, the present study demonstrates that the compromise effect is replicable in a group of younger adults (n = 27, 20–32 years of age) yet is attenuated in older adults (n = 27, 62–80 years of age). Results from an [ 18 F]-FDOPA-PET analysis in older adults indicate a positive association between older adults' inclination to engage in compromise effects and their striatal dopamine synthesis capacity. These results demonstrate altered context-dependent decision biases in older adults and suggest a neuromodulatory mechanism underlying this irregular choice. Highlights: Compromise effects (CEs) are prevalent in young but attenuated in older adults. Striatal dopamine synthesis capacity is positively related to older adults' CEs. Decision biases such as the CE require engaged cognitive functioning.